PENGEMBANGAN HUBUNGAN KOMUNIKASI ANTARPRIBADI DIKALANGAN MAHASISWA - Radja Erland Hamzah (Jurnal Pustaka Komunikasi, 2018)
The communication that takes place between individuals and individuals in the science of communication is known as interpersonal communication. Conflict in Interpersonal Relationships is one thing that differs between individuals who have relationships with one another, such as close friends, family members, and so on. The phrase having a relationship emphasizes the people who are every position and every action of others. In the context of conflict there are several ways that can be used, verbal aggressiveness and / or creative arguments. Where verbal aggression and argumentativity are two dimensions of aggressive communication. Verbal aggressiveness, a destructive form of aggressive communication, destroys individuals. Verbally verbal individuals usually hurt people who use verbal aggressive words whereas Argumentativity becomes a generally stable trait that affects individuals in communication to advocate every issue in controversial issues and verbally attack people others who use these issues. The concept of learning as constructive. this study is expected to provide assistance for the continued research of effective interpersonal relationship management models. By knowing ways of developing interpersonal relationships and conflict resolution by students who can identify and compare their students, enables users to create learning strategies tailored to the characteristics of students, and can create learning that teaches (more) conducive.